Diseño e implementación de un brazo robótico tele-operado 3DoF adaptado a un dron para manipulación y transporte de cargas livianas. - Camas Tacuri, Cristian Adrián (2022)
Although a drone can meet the physical objectives the lack of a robotic arm can be a limiting component to perform tasks of greater complexity and precision to meet this robotic system usually integrate manipulators to its mechanical structure. For this reason, this project details the adaptation of a robotic arm or 3DoF manipulator to an unmanned aerial vehicle UAV for manipulation through design and 3D printing. Together with the design, an adaptation of all the necessary electronics is implemented without intervening any sensory detection system of the UAV. The complete design of the final robotic system is presented in order to interact with it, making use of 3D display having to ability to perform different forms of manipulation and planning given by the arm. The system communicates in a tele-operated way through ROS using multiple machines connection with the purpose of lifting and moving light loads. Finally, the performance of the robotic system is presented by performing experiments both in the virtual part and in the real part